The Severity of CVB3-Induced Myocarditis Can Be Improved by Blocking the Orchestration of NLRP3 and Th17 in Balb/c Mice - Jifei Chen; Fan Yang; Song Shi; Xuexiang Liu; Fengxian Qin; Xiaomou Wei; Yujie Huang; Wenwu Liang; Lin Miao (Mediators of Inflammation)
Background. The functional characteristics of NLRP3 in the pathogenesis of coxsackievirus B3- (CVB3-) induced viral myocarditis (VMC) have not been fully elucidated, and the targeted therapeutic effect of NLRP3 or its related pathway in VMC has not been reported. Method. In this work, the change patterns of NLRP3- and Th17-related factors were detected during the pathological process of CVB3-induced VMC in Balb/c mice. The correlation between NLRP3 and Th17 cells during the VMC process was analyzed by Spearman test. The coculture system of spleen CD4+ T and bone marrow CD11c+ DC cells was set to explore the orchestration of NLRP3 and Th17 in the pathological development of VMC in vitro. Anti-IL-1β antibody or NLRP3-/- Balb/c were used to block the NLRP3 pathway indirectly and directly to analyze the NLRP3-targeting therapeutic value. Results. The change patterns of NLRP3- and Th17-related molecules in the whole pathological process of mouse CVB3-induced VMC were described. Through Spearman correlation analysis, it was confirmed that there was a close correlation between NLRP3 and Th17 cells in the whole pathological process of VMC. And the interaction mode between NLRP3 and Th17 was preliminarily explored in the cell experiment in vitro. Under the intervention of an anti-IL-1β antibody or NLRP3 knockout, the survival rate of the intervention group was significantly improved, the degree of myocardial inflammation and fibrosis was significantly alleviated, and the content of myocardial IL-17 and spleen Th17 was also significantly decreased. Conclusion. Our findings demonstrated a key role of the NLRP3 inflammasome and its close relationship with Th17 in the pathological progression of CVB3-induced VMC and suggested a possible positive feedback-like mutual regulation mechanism between the NLRP3 inflammasome and Th17 in vitro and in the early stage of CVB3 infection. Taking NLRP3 as a new starting point, it provides a new target and idea for the prevention and treatment of CVB3-induced VMC.